2017
DOI: 10.29252/archhygsci.6.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Monitoring in Leachate from Landfill Site of Qazvin, Iran

Abstract: Background & Aims of the Study: Leachate production is a major problem for solid waste landfills and causes important threat to health public and environment. One of the typical properties of heavy metals is that they cannot easily decompose in the environment. The aim of this study was to measure of heavy metals concentrations in old-age leachate from Qazvin landfill site, Iran. Materials & Methods: Sampling was conducted during summer 2014 from the leachate which was produced in Qazvin landfill site in Lia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…VMPs para os parâmetros avaliados. químico (MOR et al, 2006;MOTURI;RAWAT;SUBRAMANIAN, 2004;PANAHIFARD et al, 2017). Com relação ao cromo total, somente o PJ3 apresentou valor acima do permitido (> 0,05 mg/L).…”
Section: Qualidade Da áGua Subterrâneaunclassified
See 1 more Smart Citation
“…VMPs para os parâmetros avaliados. químico (MOR et al, 2006;MOTURI;RAWAT;SUBRAMANIAN, 2004;PANAHIFARD et al, 2017). Com relação ao cromo total, somente o PJ3 apresentou valor acima do permitido (> 0,05 mg/L).…”
Section: Qualidade Da áGua Subterrâneaunclassified
“…Outros estudos em diferentes regiões do mundo também observaram a presença de tais metais nos lixiviados e na água subterrânea (ABD EL-SALAM; ABU-ZUID, 2015;AL SABAHI et al, 2009;BECK et al, 2010;MOR et al, 2006;MOTURI;RAWAT;SUBRAMANIAN, 2004;PANAHIFARD et al, 2017). Traços de metais estão fortemente associados com o material orgânico do lixiviado e as espécies desses variam de acordo com as condições químicas do aterro, como condições de redox e pH (YOUCAI; ZIYANG, 2016), principalmente quando a disposição de resíduos ainda é recente e a fase predominante de degradação é a ácida.…”
Section: Parâmetrosunclassified
“…Wastes are not managed properly will be a source of Pb pollution, it produces leachate which is causing pollution. Fard et al [8] stated that leachate generally contains organic and inorganic compounds (heavy metals). The results of studies from MSW Landfill in Poland in 2011, the types of heavy metals found in leachate are timabl, copper, zinc, chromium, and cadmium [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, water resources including surface and ground water are to be polluted and contaminated by physical -chemical changes and ions. For these reasons the quality of these valuable resources are very important to provide healthy water supply and preserve the environment (3). In the whole global, water supplies encounter lack reliable access to clean water because of drought, low precipitation and population growth.…”
mentioning
confidence: 99%